Anger can make fake news viral online - Chuai, Yuwei; Zhao, Jichang (Frontiers in Physics, 2022)
Fake news that manipulates political elections, strikes financial systems, and even incites riots is more viral than real news online, resulting in unstable societies and buffeted democracy. While factor that drives the viral spread of fake news is rarely explored. In this study, it is unexpectedly found that the easier contagion of fake news online is positively associated with the greater anger it carries. The same results in Twitter and Weibo indicate that this correlation is independent of the platform. Moreover, mutations in emotions like increasing anger will progressively speed up the information spread. Increasing the occupation of anger by 0.1 and reducing that of joy by 0.1 are associated with the generation of nearly six more retweets in the Weibo dataset. Offline questionnaires reveal that anger leads to more incentivized audiences in terms of anxiety management and information sharing and accordingly makes fake news more contagious than real news online. Cures such as tagging anger in social media could be implemented to slow or prevent the contagion of fake news at the source.